2005
DOI: 10.3406/psy.2005.29699
|View full text |Cite
|
Sign up to set email alerts
|

Mémoire épisodique et déficit d'inhibition au cours du vieillissement cognitif : un examen de l'hypothèse frontale

Abstract: Summary : Episodic memory, inhibition deficit, and cognitive aging : An examination of the frontal hypothesis Cognitive aging is a mosaic of selective deficits and spared abilities. To account for such discrepancies, it has been assumed that age-related differences in memory tasks were mainly observed in conditions that require executive control and activation of the prefrontal cortex. The present theoretical note examines this frontal hypothesis by contrasting a strong and a weak version. The strong vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In agreement with the proposal of specific inhibitory dysfunctions in normal aging, studies that have simultaneously explored the integrity of several inhibitory processes in a single group of elderly subjects (Andrès, Guerrini, Phillips & Perfect, 2008;Charlot & Feyereisen, 2005;Kramer, Humphrey, Larish, Logan, & Strayer, 1994) demonstrated that not all inhibitory tasks were impaired in normal aging. Moreover, studies exploring inhibitory functioning in elderly subjects using verbal memory tasks do not systematically report impaired performance (i.e., Aslan et al, 2007;Sego et al, 2006; for examples of impaired performance see however Andrès et al, 2004;Radvansky et al, 1996Radvansky et al, , 2005.…”
Section: Introductionmentioning
confidence: 71%
“…In agreement with the proposal of specific inhibitory dysfunctions in normal aging, studies that have simultaneously explored the integrity of several inhibitory processes in a single group of elderly subjects (Andrès, Guerrini, Phillips & Perfect, 2008;Charlot & Feyereisen, 2005;Kramer, Humphrey, Larish, Logan, & Strayer, 1994) demonstrated that not all inhibitory tasks were impaired in normal aging. Moreover, studies exploring inhibitory functioning in elderly subjects using verbal memory tasks do not systematically report impaired performance (i.e., Aslan et al, 2007;Sego et al, 2006; for examples of impaired performance see however Andrès et al, 2004;Radvansky et al, 1996Radvansky et al, , 2005.…”
Section: Introductionmentioning
confidence: 71%
“…Indeed, encoding is strongly influenced by the level of attention allocated to the information to be memorized. A low level of attention impacts the quality of the storage as well as the facility of recovery posteriori 108 . The choice of tests evaluating episodic memory is crucial in terms of its ability to control the quality of encoding by minimizing the impact of possible fluctuations of attention level.…”
Section: Discussionmentioning
confidence: 99%
“…However, other data indicate that not all inhibitory tasks are impaired in normal aging (Charlot & Feyereisen, 2005;Kramer et al, 1994). More specifically, normal aging is characterized by an impairment of controlled0intentional inhibitory processes associated with a preservation of automatic0unintentional inhibitory processes (Andrés, 2008;Andrés et al, 2008;Collette et al, 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we were interested in comparing the integrity of these two inhibitory processes in a single group of older participants. Indeed, very few earlier studies had been interested in evaluating the generality or specificity of the inhibitory dysfunction in normal aging by simultaneously administering several tasks assessing different inhibitory processes (Andrés et al, 2008; Belleville et al, 2006; Charlot & Feyereisen, 2005; Kramer et al, 1994). In the present study, results indicate that, unlike young participants, healthy older participants seems to rely more on common cognitive resources necessary to resolve perceptual and motor conflicts (as indicated by ANOVA and correlation analyses).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation